Systematic Quality Monitoring For Specialized Palliative Care Services: Development of a Minimal Set of Quality Indicators for Palliative Care Study (QPAC). (July 2017) - Leemans, Kathleen; Deliens, L.; Van den Block, L.; Vander Stichele, R.; Francke, A. L.; Cohen, J.
Background: A feasibility evaluation of a comprehensive quality indicator set for palliative care identified the need for a minimal selection of these indicators to monitor quality of palliative care services with short questionnaires for the patients, caregivers, and family carers. Objectives: To develop a minimal indicator set for efficient quality assessment in palliative care. Design: A 2 round modified Research ANd Development corporation in collaboration with the University of California at Los Angeles (RAND/UCLA) expert consultation. Setting/Patients: Thirteen experts in palliative care (professionals and patient representatives). Measurements: In a home assignment, experts were asked to score 80 developed indicators for "priority" to be included in the minimal set on a scale from 0 (lowest priority) to 9 (highest priority). The second round consisted of a plenary meeting in which the minimal set was finalized. Results: Thirty-nine of the 80 indicators were discarded, while 19 were definitely selected after the home assignment, and 22 were proposed for discussion during the meeting; 12 of these survived the selection round. The final minimal indicator set for palliative care consists of 5 indicators about the physical aspects of care; 6 about the psychosocial aspects of care; 13 about information, communication, and care planning; 5 about type of care; and 2 about continuity of care. Conclusion: A minimal set of 31 indicators reflecting all the important issues in palliative care was created for palliative care services to assess the quality of their care in a quick and efficient manner. Additional topic-specific optional modules are available for more thorough assessment of specific aspects of care.